(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The term linguistic variation (or simply variation) refers to regional, social, or contextual. differences in the ways that a particular language is used. Variation between languages, dialects, and speakers is known as interspeaker variation. Acceptability is a concept used in linguistics to denote the intuitive judgments by users of a language on how acceptable a linguistic utterance is The linguistic utterance can be a word, a sentence, a fragment of speech in a certain dialect, or any other piece of language.